KAJIAN SOSIOLOGIS DALAM HUKUM KELUARGA ISLAM - Syamsul Arifin (Indonesian Journal of Law and Islamic Law (IJLIL), 2020)
Sociological studies in Islamic family law are an alternative to legal research, which is a legal research not only in the forms of existing rules, but also examines the law in the legal reality that occurs in society. Sociological studies become a different point of view, where Islamic family law research is very close to syara 'law, determining whether or not it is permissible according to syara'. Sociological research Sociological research can be a research explaining the phenomenon of Islamic family law studied with social theories. Moreover, the family is the smallest social structure in the social world. The study of legal practices in matters related to the Islamic family becomes legal studies not only in the form of normative doctrinal, but empirical non-doctrinal.